The Influence of PAI Teachers' Roles on Students' Morals Through the Cooperative Learning Model - Tri Hendri Herdiansyah; Fitriyani Kosasih (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the influence of the role of Islamic Education (PAI) teachers on the moral character of MTs Salafiyah students in Bandung City through cooperative learning. The urgency of this research lies in addressing the moral challenges faced by students in the digital era and highlighting the strategic role of PAI teachers in fostering moral values. A descriptive quantitative method was employed using a survey with 50 students as respondents, and the data were analyzed through simple linear regression. The results show that the role of PAI teachers has a significant positive influence on students’ moral character. This is evidenced by the t-test results with a significance value of 0.000 < 0.05 and the F-test showing 0.000 < 0.05, indicating both partial and simultaneous significant effects. The coefficient of determination (Adjusted R²) indicates that 42.4% of students’ moral development is explained by the role of PAI teachers, while 57.6% is influenced by other factors. This study contributes to the literature by emphasizing the teacher’s role as a facilitator in cooperative learning for moral education, an area that has been less explored in previous research.